Students Learning Independence from Different Specialization Classes: A Comparative Study - Sele, Yunawati; Sila, Vinsensia Ulia Rita; Oetpah, Fincensius; Kabnani, Yuliana (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The purpose of this study is to examine the learning independence of students in different specialization classes. This study employed a quantitative, comparative approach. The subjects of the study were class X SMA.  There are 21 students in class X MIPA and 36 students in class X IPS in SMA Nurul Fallah Kefamenanu. A questionnaire about learning independence was used to collect data. The results indicated that students in different specializated classes differed in their independence in learning. The learning independence of MIPA specialized students is 19.99% greater than that of IPS specialization students. This may be due to the inappropriate grouping of specialization classes and the existence of a negative stigma towards students enrolled in IPS specialization classes. This stigma has the potential to have a negative impact on self-confidence, learning motivation, learning creativity and student learning discipline. Therefore efforts that need to be made are to improve the system for determining specialization classes and to provide equal opportunities and support for each student to develop themselves according to their interests, talents and potential